2011
DOI: 10.1136/adc.2010.205971
|View full text |Cite
|
Sign up to set email alerts
|

Genital herpes in children under 11 years and investigations for sexual abuse

Abstract: Genital herpes in children under 11 years is rare. Almost a third of children diagnosed with genital herpes did not have appropriate virological investigation and few were screened for other STIs. Around a quarter of cases were referred to child protection agencies for further investigation, which limits any inferences in this study about mode of transmission in children. Sexual abuse guidance should emphasise the need for thorough assessment and investigation in cases of genital herpes in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
5
1
2
Order By: Relevance
“…Las ITS de origen viral están descritas como 1,5 veces más frecuentes que las bacterianas 5 . La aparición de infecciones por el virus del papiloma humano (VPH) o por el VHS en niños -sobre todo en menores de 11 años-siempre deben hacernos sospechar un abuso sexual, aunque en muchos de los casos no se puede confirmar 6 . Varios estudios insisten en la necesidad de hacer un cribado correcto para la detección de ITS, ya sean virales o bacterianas; incluso se habla de la importancia de realizar segundas evaluaciones, poniendo especial énfasis en que deben ser realizadas por expertos 6,7 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Las ITS de origen viral están descritas como 1,5 veces más frecuentes que las bacterianas 5 . La aparición de infecciones por el virus del papiloma humano (VPH) o por el VHS en niños -sobre todo en menores de 11 años-siempre deben hacernos sospechar un abuso sexual, aunque en muchos de los casos no se puede confirmar 6 . Varios estudios insisten en la necesidad de hacer un cribado correcto para la detección de ITS, ya sean virales o bacterianas; incluso se habla de la importancia de realizar segundas evaluaciones, poniendo especial énfasis en que deben ser realizadas por expertos 6,7 .…”
Section: Discussionunclassified
“…La aparición de infecciones por el virus del papiloma humano (VPH) o por el VHS en niños -sobre todo en menores de 11 años-siempre deben hacernos sospechar un abuso sexual, aunque en muchos de los casos no se puede confirmar 6 . Varios estudios insisten en la necesidad de hacer un cribado correcto para la detección de ITS, ya sean virales o bacterianas; incluso se habla de la importancia de realizar segundas evaluaciones, poniendo especial énfasis en que deben ser realizadas por expertos 6,7 . El VHS-2 infecta fundamentalmente e144 los genitales, siendo frecuentes las recurrencias (como ocurrió en nuestro caso) hasta que consigan mantener un nivel estable de anticuerpos, siendo posible difundir el virus mientras se es portador 8 .…”
Section: Discussionunclassified
“…Genital herpes in children under the age of 11 is rarely seen, with a rate of about 1/1000000. In one-third of these cases, no viral investigation was established, and in a very small fraction, other sexually transmitted diseases were found (13). While in adults, sexual transmission is common, it has been reported that in cases below the age of 5, anogenital herpes can be contracted by nonsexual routes.…”
Section: Genital Herpes Is a Viral Infection Caused By Hsvmentioning
confidence: 99%
“…In the existing literature, it has been reported that in examinations of children with herpetic lesions in England, HSV-1 was found to be more common than HSV-2 (14), which also indicates that non-sexual infection is more common (13). When encountering genital herpes, it is important to carry out HSV serotyping.…”
Section: Genital Herpes Is a Viral Infection Caused By Hsvmentioning
confidence: 99%
See 1 more Smart Citation